Midwives’ experiences following the conclusion of a Nursing and Midwifery Council Fitness to Practise Referral: a phenomenological study - Corr, Alison (2025)
Background: The Nursing and Midwifery Council (NMC) is an independent regulatory organisation which dictates the standards for practice and education for midwives, and undertakes fitness to practise (FtP) investigations when concerns are raised regarding a midwife’s practice or conduct. Yet, institutions that monitor health and social care regulators in the UK have criticised the NMC’s own practices, condemning the length of time taken to conclude referrals. Concerns have also been raised regarding the possible effects an FtP referral could have on registrants’ health and well-being, however this has not been researched.